The Effect of Reciprocal Strategy and Learning Style on Reading Comprehension of the 10th Grade Students of SMAN 3 Amlapura - Hari Sukrawan, I Made (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2012)
ABSTRACT The Effect of Reciprocal Strategy and Learning Style on Reading Comprehension of the 10th Grade Students of SMAN 3 Amlapura. Thesis, Language Education Study Program, Post Graduate Program, Ganesha University of Education. Key Words: reciprocal teaching strategy, learning style, and reading comprehension. This study aimed at investigating the effects of reciprocal teaching and learning style on the English reading comprehension of 10th grade students of SMAN 3 Amlapura. The research subjects of this study were the 10th grade students of SMAN 3 Amlapura. There were 180 students involved as the research subjects of this study. This study was a quasy experiment. The data were collected quantitatively. The data were collected using two types of instruments: test and questionnaire. The method of data analysis used was two-way ANOVA. The study concluded that the use reciprocal strategy significantly improve students? reading comprehension of the 10th grade students of SMA Negeri 3 Amlapura. Reciprocal strategy is also significantly improve visual-dominant students in reading comprehension. There was no significant difference in students' reading comprehension between the two groups of students who were dominant in Kinestatic learning style treated with learning style.